PENGARUH RISIKO AUDIT DAN LAMANYA WAKTU AUDIT TERHADAP PENETAPAN AUDIT FEE - Tina Hartati Saputri; Herma Wiharno; Enung Nurhayati (Program Studi Akuntansi, Universitas Kuningan, 2017)
The problem is an issue fee of a dilemma because the auditor received a fee from the company (client) to be audited. The purpose of this study to investigate the effect of audit risk and length of time of the determination of audit fee audit either simultaneously or partial. The object of this study is the auditor of public accounting firm in Bandung.This research method using descriptive and verification methods analyst. This study uses 8 public accounting firms and 100 auditors working in 8 shades that have been audited sample. As well as the technique used is purposive sampling analysis techniques, as well as the technique used is the technique of multiple linear regression analysis with the help of SPSS version 20.The results of this study showed that simultaneous Fhitung = 48.382 F table = 3.12 then Ho is rejected and Ha accepted, meaning that the risk of an audit, and the length of time the audit simultaneously significant effect on the determination of the audit fee. In the test Partial obtained the value t = 3.112 table = 1.666 then Ho is rejected and Ha accepted, meaning that audit risk positive and significant impact on the determination of the audit fee, and t = 4.826 table = 1.666 then Ho is rejected and Ha accepted, meaning the length of time the audit positive and significant impact on the determination of the audit fee.From the results of research and discussion can be concluded that simultaneous audit risk and the length of time the audit affect the determination of audit fee survey on auditor Public Accounting Firm in Bandung, then partially, audit risk positive effect on the determination of the audit fee and the length of time the audit positive effect on the determination audit fee.Keywords: Determination of The Audit Fee, Audit Risk, Duration of Audit